Islamisasi Ilmu dalam Upaya Mengatasi Keterbelakangan Kualitas Umat Islam di Era Modern - Della Putri Aprillianti; Lailatus Sa'adah; Aulia Tegas Wicaksono; M. Fadli Al-Ghifary; Syahidin Syahidin; Muhamad Farhan (STIKes Ibnu Sina Ajibarang, 2024)
Education is important in human progress. Likewise, Islamic education plays a very important role in determining the quality of life of Muslims. Unfortunately, in this modern era it can be clearly felt that Islamic education is lagging behind modern western education. According to Al-Faruqi an Al-Attas' view, this is evidenced by the existence of an identity crisis, the loss of economic, political and intellectual independence in the Islamic world, the existence of sectarianism that focuses on borders rather than development, and the slow adoption of new technology and modernization (Ramdhani, 2013). There are several factors that cause these things, namely: the influence of western science and philosophy, colonialism, lack of Islamic unity and lack of modernization of the Islamic world. To overcome these problems, several ulama proposed the Islamization of science. This article was created to discuss the concept of Islamization of science using the SLR method. The Islamization of Science aims to integrate Islamic principles and values into the field of science and knowledge which involves a process of rethinking, re-evaluating and reconstructing scientific knowledge to enrich the vision and struggle of Islam (Sahide, 2015). The concept of Islamization of Science was introduced by Ismail Raji Al-Faruqi who defined it as an effort to integrate science into the unity of Muslim life. Which aims to improve the quality of Islamic education, and it is hoped that it can also improve the quality of life of Muslims in this era.